A Retrospective Observational Study to Assess Outcomes in Pregnant Women with Cardiac Complications in Obstetrics and Gynecology Department in Tertiary Care Center - Ramayanam, Navakanth Raju (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: To evaluate maternal outcomes in pregnant women with heart complications, focusing on age, delivery method, baby weight, APGAR scores, and major complications. Material and Methods: This retrospective observational study was conducted at Sri Venkateshwara Institute of Medical Sciences, Tirupati, India. The study involved 90 participants, with data collected on maternal age, delivery methods, baby weight, APGAR scores, and major complications. Ethical approval was obtained from the Institutional Ethical Committee to ensure adherence to ethical standards. Result and Discussion: The age distribution of participants ranged from 18 to 40 years, with 46% aged 24-29 years and 40% aged 18-23 years. Cardiac dysfunction was present in 28% of patients, and 24% had congenital heart disease (CHD). The findings highlight the importance of identifying high-risk age groups and understanding the prevalence of cardiac conditions such as cardiac dysfunction and CHD among pregnant women. Monitoring stillbirth rates and assessing infant responsiveness through APGAR scores are critical. Proactive management strategies are essential to mitigate morbidity associated with pregnancy-related complications. Conclusion: The study underscores the significance of cardio-obstetrics in managing cardiovascular health during pregnancy. By identifying high-risk groups and complications, healthcare providers can adopt proactive strategies to improve maternal and fetal outcomes.